2013
DOI: 10.1186/1756-8722-6-62
|View full text |Cite
|
Sign up to set email alerts
|

Fibroblast growth factor-2 (FGF2) and syndecan-1 (SDC1) are potential biomarkers for putative circulating CD15+/CD30+ cells in poor outcome Hodgkin lymphoma patients

Abstract: BackgroundHigh risk, unfavorable classical Hodgkin lymphoma (cHL) includes those patients with primary refractory or early relapse, and progressive disease. To improve the availability of biomarkers for this group of patients, we investigated both tumor biopsies and peripheral blood leukocytes (PBL) of untreated (chemo-naïve, CN) Nodular Sclerosis Classic Hodgkin Lymphoma (NS-cHL) patients for consistent biomarkers that can predict the outcome prior to frontline treatment.Methods and materialsBioinformatics da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
24
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 62 publications
1
24
0
Order By: Relevance
“…Moreover, ELISA data demonstrated high FGF2 protein amounts in the supernatants of the cell lines HDLM-2 and KM-H2 ( Fig 5B ), indicating active autocrine FGF2-signalling in KM-H2. Enhanced expression of FGF2, FGFR2 and FGFR3 was detected in HL patient samples in silico ( S3 Fig ), supporting a general activation of this pathway in HL as described recently [ 49 , 50 ]. Treatment of KM-H2 cells with recombinant FGF2 protein yielded no change in OTX2 transcription ( Fig 5C ), consistent with saturated autocrine FGF2 activity in this cell line.…”
Section: Resultssupporting
confidence: 87%
“…Moreover, ELISA data demonstrated high FGF2 protein amounts in the supernatants of the cell lines HDLM-2 and KM-H2 ( Fig 5B ), indicating active autocrine FGF2-signalling in KM-H2. Enhanced expression of FGF2, FGFR2 and FGFR3 was detected in HL patient samples in silico ( S3 Fig ), supporting a general activation of this pathway in HL as described recently [ 49 , 50 ]. Treatment of KM-H2 cells with recombinant FGF2 protein yielded no change in OTX2 transcription ( Fig 5C ), consistent with saturated autocrine FGF2 activity in this cell line.…”
Section: Resultssupporting
confidence: 87%
“…In line with this, increased expression of FGF2 and SDC1 was also reported in HL cell lines [68]. Overall, findings suggest that increased expression of FGF2, FGFR, and SCD1 is associated with poor prognosis and chemoresistance [62]. …”
Section: Roles Of Fgf2 In Tumor Progressionmentioning
confidence: 59%
“…HRS cells not only produce but also have the ability to secrete VEGF [17]. Another study found over-expression of FGF-2 in these cells, and this was confirmed by the study of RT-PCR [23].…”
Section: Role Of Expression Of Proangiogenic Factorsmentioning
confidence: 74%
“…The potential of HRS cells to stimulate angiogenesis was shown in in vitro studies [17,23]. HRS cells not only produce but also have the ability to secrete VEGF [17].…”
Section: Role Of Expression Of Proangiogenic Factorsmentioning
confidence: 99%